2023
DOI: 10.3389/fcimb.2023.1108228
|View full text |Cite
|
Sign up to set email alerts
|

Excessive neutrophil extracellular trap formation induced by Porphyromonas gingivalis lipopolysaccharide exacerbates inflammatory responses in high glucose microenvironment

Abstract: IntroductionNeutrophil extracellular trap (NET) is a novel defense strategy of neutrophils and found to be induced by Porphyromonas gingivalis (P. gingivalis) lipopolysaccharide (LPS) or high glucose. The aim of this study was to investigate the roles and mechanisms of NET formation in high glucose inflammatory microenvironment.MethodsNETs induced by 1 μg/ml P. gingivalis LPS and/or 25 mM glucose were visualized using a fluorescence microscopy and the levels of extracellular DNA were determined by a microplate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In addition, these authors also detected increased levels of intracellular Ca 2+ and PAD4 in stimulated neutrophils (Chen et al, 2022). Other authors have also demonstrated that neutrophil exposure to LPS from P. gingivalis significantly increased NET release in vitro (Alizadehgharib et al, 2021; Tong et al, 2023).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, these authors also detected increased levels of intracellular Ca 2+ and PAD4 in stimulated neutrophils (Chen et al, 2022). Other authors have also demonstrated that neutrophil exposure to LPS from P. gingivalis significantly increased NET release in vitro (Alizadehgharib et al, 2021; Tong et al, 2023).…”
Section: Discussionmentioning
confidence: 92%
“…Neutrophil was isolated and purified (purity > 90%) from mice (Figure S3A-S3C). Then, we stimulated the isolated neutrophils with LPS which has been confirmed as the classical inducer of NETs 31 . We tested the induction of NETs formation by different concentrations of LPS and found that the most appropriate concentration was 5 μg/mL (Figure S3D-S3E).…”
Section: Resultsmentioning
confidence: 99%